การหาสหสัมพันธ์ระหว่างอัตราส่วนของแมงกานีสและเหล็กในทัวร์มาลีนที่ผ่านการฉายรังสีแกมมากับการเปลี่ยนสี - อภิเชษฐ์ มณีวงษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
In this research, tourmaline samples were irradiated by gamma ray from Cobalt-60 at various doses of 600, 800 and 1,000 kGy in order to observe whether or not the color change was caused by ratios of manganese and iron content in the samples. Manganese and iron content were analyzed by neutron activation analysis. From the experimental results, the green tourmaline with Mn/Fe ratio of 0.15 to 0.55 found not to give clearly changes in color. Intensification of pink color to red was observed with Mn/Fe ratio of 0.97 to 7.73 but not as significant as those of with Mn/Fe ratio of 51.50-80.50 and the bi-color tourmaline with Mn/Fe ratio of 163.00 to 177.00. It was concluded that pink tourmaline samples with Mn/Fe ratio of greater than 51.50 and the bi-color tourmaline samples with Mn/Fe ratio of greater than 163.00 were found to give clearly change to deep color which apparently make value added to the original samples.